ANALISIS INFORMASI CITRA ANATOMI MSCT SCAN ORBITA POTONGAN AXIAL DENGAN VARIASI KERNEL DENGAN WINDOW SINUS DAN WINDOW BASE ORBITA PADA KASUS TRAUMA - Endang Dwi Endarti; Jeffry Ardianto; Andrey Nino Kurniawan (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background: Trauma on the Orbits is very precisely evaluated by MSCT Scan and can analyze well the bone structure and surrounding soft tissue. One of the main parameters on MSCT Scan is the algorithm or kernel reconstruction. The improper use of the kernel can affect spatial resolution and contrast resolution, so evaluating MSCT Scan image information of Orbits with the use of window and the kernel variation is the main problem discussed. The purpose of this study was to determine differences in anatomical information on MSCT Scan of Orbits images with sinuses window variations and base orbits window with kernel of H30s Medium Smooth, H40s Medium, H70s Sharp in trauma cases and find out the best window and kernel variations in displaying anatomical information of Orbits MSCT Scan. Methods: This research is quantitative research. The research subjects were 2 Radiology Specialists as research respondents. The sample used was 10 patients. The raw data acquisition that has been obtained is reconstructed into a sinuses window and orbits base window with kernel H30s Medium Smooth, H40s Medium, H70s Sharp. Data obtained between respondents were carried out by the Cohen’s Kappa test, then the Friedman test with significance <0.05 and the best variation was obtained from the mean rank Friedman test. Results: The results of the study show that. In the variation of medium smooth H30s window and medium H40s and very sharp H70s sinus window featuring orbital walls. and most clearly in the sinus window H70s very sharp. In the window base the orbitals H30s medium smooth and H40s medium. Show clarity in the anterior chamber, lens and medial rectus muscle. Conclusion: The orbital H70s window base is very sharp showing clarity on the optic nerve, anterior chamber, lateral rectus muscle and orbital wall. Based on the results of the mean rank, the Friedman test showed that variations in the orbits window base with the Sharp H70s kernel were the best variations in each anatomic area.